Usefulness of SPINA model in evaluation of the thyroid function in euthyroid pediatric patients children with subclinical hypothyroidism - Giannakopoulos, Aristeidis; Efthymiadou, Alexandra; Kritikou, Dimitra; Chrysis, Dionisios (Frontiers in Endocrinology, 2025)
ObjectiveSubclinical hypothyroidism (SH) is biochemically defined by increased TSH and normal thyroid hormones, and its management is a matter of debate. Herein, we investigated thyroid function in euthyroid and children with SH using a structure parameter inference approach (SPINA) model along with published data from population-based TSH-FT4 curves.DesignThe study included 183 children and adolescents with SH and 313 healthy controls. The predicted and actual secretory capacity of thyroid gland (SPINA-GT) was calculated in all euthyroid children divided into quartiles according to TSH values, and in children with SH, which were further subcategorized into those with mild SH (TSH: 4.5 – 10 mIU/L) and severe SH (TSH > 10 mIU/L).ResultsActual SPINA-GT values decreased significantly from the 1st to the 2nd quartile of normal TSH values in euthyroid children (p< 0.001). It was also significantly decreased in mild SH compared to the upper 2 TSH quartiles of euthyroid range, and in severe SH compared to mild SH. Actual SPINA-GT values were significantly decreased from predicted SPINA-GT values in the upper 2 quartiles of TSH in euthyroid children and in children with mild and severe SH. Thyroid antibody positivity was statistically higher in the SH group (11.3%) compared to the euthyroid group (6.4%).ConclusionThe implementation of SPINA model for thyroid function gives a wider perspective of thyroid gland’s performance within the euthyroid range of TSH, as well as in SH and add to the discussion for the nature of SH, and the necessity of its management.